Heterozygous Mylk3 Knockout Mice Partially Recapitulate Human DCM With Heterozygous MYLK3 Mutations - Tougas, Carson L.; Grindrod, Tabor; Cai, Lawrence X.; Alkassis, Fariz F.; Kasahara, Hideko (Frontiers in Physiology, 2019)
Backgrounds: Recent studies identified heterozygous variants in MYLK3 gene that encodes cardiac myosin light chain kinase (cMLCK) are related to familial dilated cardiomyopathy (DCM) for the first time. Autosomal dominant traits suggest that pathogenesis of DCM could be related to heterozygous MYLK3 loss-of-function variants (haploinsufficiency). We previously generated and examined homozygous Mylk3 knockout mice that lead to heart failure. It had yet to be examined whether heterozygous Mylk3 knockout mice represent a DCM-like phenotype. Methods and Results: Heterozygous knockout (Mylk3wild/-) mice were examined regarding cardiac function, heart histology and expression of cMLCK protein and mRNA relative to age-matched wild-type controls (Mylk3wild/wild). At 4 months of age, cardiac contractility in heterozygous knockout mice was reduced with percent fractional shortening of 23.0  1.2% comparted to 30.0  1.7% in control (Mylk3 wild/- vs. Mylk3wild/wild, n=9 each). In 4-month-old heterozygous knockout hearts, expression of cMLCK mRNA was expectedly reduced by almost half, however protein expression was reduced by approximately 75% relative to the control wild-type (Mylk3 wild/- vs. Mylk3wild/wild, n=9 each). Isolated ventricular cardiomyocytes from heterozygous knockout mice were larger with increase of short-axis length relative to the cardiomyocytes from control mice. However, increase of heart failure markers as well as interstitial fibrosis were not evident in heterozygous knockout mice compared to controls. Conclusion: Heterozygous Mylk3 knockout mice show mild reduction of cardiac contractility by 4 months of age, and proteins reduced by approximately 75% relative to the control wild-type mice. These mice partly resemble human with the heterozygous MYLK3 mutation, but the reduction in cardiac contractility was milder.